Formation mechanism and characterization of immiscible nanoporous binary Cu–Ag alloys with excellent surface-enhanced Raman scattering performance by chemical dealloying of glassy precursors. Issue 5 (27th January 2020) - Wang, Jing; Liu, Xiongjun; Li, Rui; Li, Zhibin; Wang, Xianzhen; Wang, Hui; Wu, Yuan; Jiang, Suihe; Lu, Zhaoping
Abstract : Immiscible nanoporous binary Cu–Ag (NPCA) alloys with customizable microstructures and excellent SERS performance have been developed by dealloying metallic glasses. Abstract : Nanoporous binary alloys with customizable microstructures and unique properties are desirable for engineering applications in nanotechnology. In this work, a three-dimensional immiscible nanoporous Cu–Ag (NPCA) alloy with tunable porosity has been fabricated by dealloying Cu–Zr–Al–Ag metallic glasses. The relationship between the composition, dealloying time and temperature, and nanoporosity was systematically investigated. It has been found that addition of Ag substantially slows down the dealloying process, and a composition threshold (∼10 at% Ag) exists to form a uniform nanoporous structure for the Cu–Zr–Al–Ag glassy precursor. The evolution of the NPCA ligament size with dealloying time and temperature can be well described by a diffusion-based growth kinetic model. Moreover, the addition of Ag effectively enhances the surface enhanced Raman scattering (SERS) performance of the resultant nanoporous materials. The highest SERS enhancement factor (EF) of NPCA resulting from the precursor with 10 at% Ag content is 6 × 10 6, which is about 60 times greater than that of the nanoporous copper (NPC) without Ag, and the limit of detection (LOD) is 10 −11 mol L −1 to R6G. Our findings not only provide new insight into the formation mechanism of immiscible nanoporous alloys, but also are helpful for developing inexpensive SERS substrates with multiple metallic elements.